La sàbia Sibilla in Sardegna tra cultura dotta e popolare. - STRINNA, GIOVANNI (Scripta)
The myth of the Sibyl had a great resonance in Western culture, from Antiquity to the Modern Age, and reverberated through the literary, liturgical-musical and artistic traditions, being used for different ideological purposes, sometimes for didactic and religious, at other times for propaganda. Even the Kingdom of Sardinia, which between the end of the Middle Ages and the Modern Age was part of the Crown of Aragon and then the Kingdom of Spain, incorporated some of these traditions, and this contribution identifies their traces on some levels, in particular those of folklore and art.